In the Wake of the Global Economic Crisis : Adjusting to Lower Revenue of the Southern African Customs Union in Botswana, Lesotho, Namibia, and Swaziland - Fontaine, Thomson (Departmental Papers; Departmental Paper ;, 2011)
The Southern African Customs Union (SACU) is facing its biggest challenge in its 100 years of existence. The global economic crisis has significantly reduced its revenue outlook, which is having a disproportionate impact on its smaller member countries, and which calls for an appropriate policy response. This paper discusses specifically the implications for Botswana, Lesotho, Namibia, and Swaziland, and provides recommendations regarding the proper fiscal response by these countries to the decline in SACU revenue.